Rzeczy niemieckie w poezji Joanny Ziembińskiej-Kurek i Marka Lobo Wojciechowskiego - Mirosława Szott (In Gremium. Studies in History, Culture and Politics, 2015)
German things in the poetry of Joanna Ziembińska -Kurek and Marek Lobo WojciechowskiThe poetry of the Polish-German border, which is Lubusz, often shows the role of things in the chain of historical events. The double origin of these lands is the starting point for considering the category of inanimate matter for the Lubusz writers. Concentrating on subjects of German provenance is visible especially in the poetry of Joanna Ziembińska-Kurek and Marek Lobo Wojciechowski. Each of these authors is biographically associated with a different place; and so Ziembińska – with Sulęcin (GER Zielenzig), Wojciechowski – with GorzówWielkopolski (GER Landsberg).In this article there is recalled the classification by Joanna Szydłowska (the researcher has proposed eight categories, according to which the meaning of things in post-Yalta Occident can be considered). The circle of issues associated with the circulation of objects and change of their owners will prove to be the most important for this article. It is the axis linking the world of the objects in the poetry of these authors.